Method for Providing an Aqueous Composition Having Retroreflective Properties - Patent application
By adding backglass glass beads and specific thickeners to water-based coatings, paints, inks or coating preparations, the problem of difficult recovery properties and instability of the coating in the prior art is solved, and efficient and uniform return effects are achieved.
Patent Information
- Application Number
- JP2022549719
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-02-25
- Filing Date
- 2021-02-24
- Publication Date
- 2025-04-02
- Estimated Expiration
- 2041-02-24
AI Technical Summary
The prior art is difficult to effectively provide backgloss properties for water-based coatings, paints, inks and coating formulations, and the addition of backgloss glass beads can lead to instability and unevenness of the coating.
Using a water-based pseudoplastic gel composition comprising a water-based coating, paint, ink or coating formulation, retroglass glass beads and specific thickeners, a specific thickener is mixed to obtain a suitable viscosity and ensure a uniform distribution of the glass beads.
It achieves the ability to provide backlight properties for water-based coatings, paints, inks and coating preparations without changing the fluidity of the raw coatings, and ensures the stability and uniformity of the product.
Smart Images

Figure 0007655928000011 
Figure 0007655928000012 
Figure 0007655928000013
Abstract
Description
Detailed Description of the Invention
[0001] [Field of the Invention] The present invention relates to a method for providing a composition selected from the group consisting of water-based pastes, inks, paints and coating formulations having retroreflective properties. The present invention further relates to said method further comprising the step of applying the retroreflective composition to a substrate.
[0002] [Background of the invention] Retroreflective effects are used in a variety of applications, such as to improve the visibility of road signs, road markers, fabrics, cars, etc. in dark conditions, or simply to improve their visual appearance. Road markers are typically given retroreflective properties by adding spherical glass beads with a specific refractive index. Retroreflection occurs due to the combined effects of refraction of incident light through the top surface of the spherical glass beads, internal reflection from the bottom outer surface of the spherical glass beads, and then refraction of light as it exits the top surface of the spherical glass beads back in the direction from which it came.
[0003] WO 00 / 42113 A1 relates to a retroreflective ink comprising microbeads in a liquid carrier medium. The liquid carrier medium may be water. The ink is intended for screen printing.
[0004] WO 2004 / 017104 A2 discloses a retroreflective composition comprising retroreflective microspheres, a binder system, and a thixotropic blend comprising at least two thixotropic agents in an amount of about 2 to about 5% by weight based on the retroreflective composition. The composition may also include water. The retroreflective compositions are intended for use as paints, inks, and coatings and are applied to a substrate using a propellant-driven aerosol applicator.
[0005] Water-based paste, paint, ink and coating formulations are commercially available in a variety of colors and / or designed for a variety of applications by many suppliers. Each new application and improvement of a water-based paste, paint, ink or coating formulation requires a costly and time-consuming development process from laboratory samples to commercial products. Obviously, offering a large number of products in a variety of colors and / or for a variety of applications requires large warehouses and extensive stockpiles to be able to respond quickly to customer orders.
[0006] As outlined above, imparting retroreflective properties to paste, paint, ink and coating formulations can be advantageous as it results in improved visibility and / or a more attractive visual appearance. The development of retroreflective versions of already commercially available water-based paste, paint, ink and coating formulations also requires a costly and time-consuming development process, since the addition of additional components, including retroreflective spherical glass beads, should not adversely affect the processability of existing paste, paint, ink or coating formulations, let alone the properties of the paste, paint, ink or coating formulation after drying or curing. Providing retroreflective paste, paint, ink and coating formulations in addition to those that do not have retroreflective properties also requires huge warehouses.
[0007] Thus, there is a need for an efficient method for providing water-based paste, paint, ink and coating formulations with retroreflective properties, i.e., commercially available water-based paste, paint, ink and coating formulations, on demand, without substantially changing the processability of the water-based paint, ink and coating formulations and without adversely affecting the properties of the paste, paint, ink or coating formulation after drying or curing.
[0008] We measured the rheological properties of the rheometer with plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C. -1It has been determined that providing water-based paste, paint, ink and coating formulations with retroreflective properties, having a viscosity of 0.25 to 1000 Pa·s at a shear rate of 100 Hz, cannot be achieved by simply mixing the water-based paste, paint, ink or coating formulation with retroreflective spherical glass beads, as this would result in inhomogeneity, air entrapment and / or instability in the distribution of the spherical glass beads throughout the composition.
[0009] It is therefore an object of the present invention to provide an efficient method for providing water-based paste, paint, ink and coating formulations with retroreflective properties without substantially changing the processability of the water-based paste, paint, ink and coating formulations and without adversely affecting the properties of the paste, paint, ink or coating formulation after drying or curing.
[0010] It is a further object of the present invention to provide an efficient method for providing water-based paste, paint, ink and coating formulations containing retroreflective spherical glass beads that results in a homogenous and storage stable distribution of the retroreflective spherical glass beads throughout the composition.
[0011] [Summary of the Invention] The inventors have discovered that water-based paste, paint, ink or coating formulations that do not have retroreflective properties can be transformed into aqueous pseudoplastic gel compositions containing retroreflective spherical glass beads and specific thickeners, with a 0.01s -1 The first viscosity is 5 to 250 Pa s at a shear rate of 100 s -1 It has been unexpectedly determined that one or more of the objectives may be achieved by mixing an aqueous pseudoplastic gel composition having a second viscosity that is 10 to 1000 times lower than the first viscosity at a shear rate of 100 / ml, and optionally thereafter adding additional thickening agent.
[0012] Thus, in a first aspect, the present invention provides a method for providing a composition selected from the group consisting of water-based paste, ink, paint and coating formulations having retroreflective properties, said method comprising: a) providing a water-based paste, ink, paint or coating formulation having no retroreflective properties, said water-based paste, ink, paint or coating formulation having a reflectance of less than 0.01 s -1 having a viscosity η1 of 0.25 to 1000 Pa s at a shear rate of b) 0.01s -1 The first viscosity η2 of 5 to 250 Pa·s at a shear rate of 100 s -1 and preparing an aqueous pseudoplastic gel composition having a second viscosity η3 that is 10 to 1000 times lower than the first viscosity η2 at a shear rate of 100 to 1000 times the shear rate of the aqueous pseudoplastic gel, based on the total weight of the aqueous pseudoplastic gel composition. 15 to 39.85% by weight of water, 60-80% by weight of spherical glass beads having a median particle diameter D50 of 5-1500 μm, preferably 20-150 μm, measured by laser diffraction, and a refractive index of 1.8-2.8, measured at a wavelength λ of 589 nm, optionally at least a portion of the spherical glass beads being hemispherically coated with a light-reflecting coating, 0.15 to 2.50% by weight of a thickening agent, and 0-5% by weight of one or more further ingredients and c) mixing the aqueous paste, ink, paint or coating formulation provided in step (a) with the aqueous pseudoplastic gel composition provided in step (b) in a weight ratio of 30:70 to 70:30; d) mixing the mixture obtained in step (c) with 0-2 wt. % of a thickener, based on the total weight of the aqueous paste, ink, paint or coating formulation having retroreflective properties, to provide an aqueous paste, ink, paint or coating formulation having retroreflective properties. The viscosities η1, η2 and η3 are measured at a temperature of 25° C. in a rheometer with a plate-plate geometry and a gap distance of 0.5 mm; It concerns the method.
[0013] The aqueous pseudoplastic gel composition is mainly composed of water and spherical glass beads. The inert spherical glass beads have no or little effect on aqueous paste, ink, paint or coating formulations. Therefore, these systems have high compatibility with aqueous paste, ink, paint or coating formulations. Water disappears from the paste, ink, paint or coating formulations by drying or curing. The inventors have confirmed that the processability of aqueous paste, paint, ink and coating formulations is hardly changed when the aqueous pseudoplastic gel composition is added in a suitable amount. Since the retroreflective spherical glass beads are added in the form of a stable and homogeneous aqueous pseudoplastic gel composition, they can be added to aqueous paste, ink, paint or coating formulations (which do not have retroreflective properties) without air entrainment, resulting in a stable and homogeneous aqueous paste, ink, paint or coating formulation with retroreflective properties.
[0014] [Definition] The term "pseudoplastic gel", as used herein, refers to a gel that exhibits shear thinning behavior and does not have a yield point.
[0015] The term "shear thinning behavior" as it relates to the pseudoplastic gels of the present invention refers to the decrease in viscosity when the pseudoplastic gel, initially under static conditions, is subjected to a shear rate.
[0016] The term "tan(δ)" (δ is the phase shift) is defined as the ratio G" / G', as commonly known in the art of rheology. G" represents the loss modulus and characterizes the viscous or liquid-like behavior of the sample. G' represents the storage modulus and characterizes the elastic or solid-like behavior of the sample. If the sample exhibits purely viscous and no elastic behavior, then δ=90°, G'=0 and tan(δ)=∞. If the sample exhibits purely elastic and no viscous behavior, then δ=0°, G"=0 and tan(δ)=0. If the sample has a non-zero phase shift δ of less than 45°, then tan(δ) is less than 1, G' is greater than G", and the sample exhibits gel-like behavior in that the elastic behavior dominates over the viscous behavior. [Brief description of the drawings]
[0017] [Figure 1] FIG. 2 shows the viscosity versus shear rate profile of an aqueous pseudoplastic gel composition used in a process according to the present invention. [Diagram 2] FIG. 2 shows the thixotropic behavior of the aqueous pseudoplastic gel composition of FIG. 1. [Diagram 3] FIG. 2 shows the tan(δ) profile as a function of oscillation frequency for the aqueous pseudoplastic gel composition used in the process according to the invention.
[0018] [Detailed Description] In a first aspect, the present invention provides a method for providing a composition selected from the group consisting of water-based paste, ink, paint and coating formulations having retroreflective properties, the method comprising: a) providing a water-based paste, ink, paint or coating formulation having no retroreflective properties, said water-based paste, ink, paint or coating formulation having a reflectance of less than 0.01 s -1 having a viscosity η1 of 0.25 to 1000 Pa s at a shear rate of b) 0.01s -1 The first viscosity η2 of 5 to 250 Pa·s at a shear rate of 100 s -1 and preparing an aqueous pseudoplastic gel composition having a second viscosity η3 that is 10 to 1000 times lower than the first viscosity η2 at a shear rate of 100 to 1000 times the shear rate of the aqueous pseudoplastic gel, based on the total weight of the aqueous pseudoplastic gel composition. 15 to 39.85% by weight of water, 60-80% by weight of spherical glass beads having a median particle diameter D50 of 5-1500 μm, preferably 20-150 μm, measured by laser diffraction, and a refractive index of 1.8-2.8, measured at a wavelength λ of 589 nm, optionally at least a portion of the spherical glass beads being hemispherically coated with a light-reflecting coating, 0.15 to 2.50% by weight of a thickening agent, and 0-5% by weight of one or more further ingredients and c) mixing the aqueous paste, ink, paint or coating formulation provided in step (a) with the aqueous pseudoplastic gel composition provided in step (b) in a weight ratio of 30:70 to 70:30; d) mixing the mixture obtained in step (c) with 0-2 wt. % of a thickener, based on the total weight of the aqueous paste, ink, paint or coating formulation having retroreflective properties, to provide an aqueous paste, ink, paint or coating formulation having retroreflective properties. wherein the viscosities η1, η2 and η3 are measured at a temperature of 25° C. in a rheometer with plate-plate geometry and a gap distance of 0.5 mm.
[0019] In preferred embodiments, the aqueous pseudoplastic gel composition provided in step (b) is stable for at least 1 day, more preferably at least 2 days, at least 5 days, at least 10 days, at least 1 month, at least 2 months, at least 6 months, at least 1 year, at least 2 years, and the composition is considered stable when no settling, syneresis and separation can be observed upon visual and tactile inspection.
[0020] In other preferred embodiments, the aqueous paste, ink, paint or coating formulation with retroreflective properties obtained in step (d) is stable and homogeneous for at least 1 day, more preferably at least 2 days, at least 5 days, at least 10 days, at least 1 month, at least 2 months, at least 6 months, at least 1 year, at least 2 years, and the composition is considered stable and homogeneous when no settling, syneresis and separation can be observed upon visual and tactile inspection and no air inclusion can be visually observed upon inspection with a microscope camera.
[0021] In a preferred embodiment, the water-based paste, ink, paint or coating formulation without retroreflective properties provided in step (a) has a reflectance of less than 0.01 s -1and a viscosity η1 of 0.25-900 Pa·s, 0.25-800 Pa·s, 0.25-700 Pa·s, 0.25-600 Pa·s, 0.25-500 Pa·s, 0.25-400 Pa·s, or 0.25-300 Pa·s at a shear rate of 100 s, the viscosity being measured at a temperature of 25 °C in a rheometer with plate-plate geometry and a gap distance of 0.5 mm.
[0022] In another preferred embodiment, the water-based paste, ink, paint or coating formulation without retroreflective properties provided in step (a) has a reflectance of less than 0.01 s -1 and a viscosity η1 of 1-1000 Pa·s, 10-1000 Pa·s, 100-1000 Pa·s, 150-1000 Pa·s, 200-1000 Pa·s, or 250-1000 Pa·s at a shear rate of 100° C., the viscosity being measured at a temperature of 25° C. in a rheometer with plate-plate geometry and a gap distance of 0.5 mm.
[0023] In step (c), the aqueous paste, ink, paint or coating formulation provided in step (a) is preferably mixed with the aqueous pseudoplastic gel composition provided in step (b) in a weight ratio of 60:40 to 40:60, more preferably in a weight ratio of 45:55 to 55:45.
[0024] In a preferred embodiment, the method defined herein further comprises the step of applying the aqueous paste, ink, paint or coating formulation having retroreflective properties obtained in step (d) to a substrate using screen printing, spray coating or spray painting.
[0025] In a preferred embodiment, steps (c) and (d) are carried out at a temperature of 15 to 30° C., preferably for a period of at least 5 minutes.
[0026] (spherical glass beads) As previously defined herein, the refractive index of the spherical glass beads, measured at a wavelength λ of 589 nm, is between 1.8 and 2.8.
[0027] In a preferred embodiment, the term "glass" in "spherical glass beads" as used herein refers to a non-crystalline amorphous solid and transparent material made of oxides. In another embodiment, the term "glass" in "spherical glass beads" refers to a solid and transparent material made of oxides and containing some degree of crystallinity. The refractive index of spherical glass beads is closely related to the density of glass, although the relationship is not linear. Due to the nature of glass, the density is approximately an additive function of its composition. The density of spherical glass beads with a refractive index of 1.5 to 2.8 is typically 2.5 to 4.5 g / cm. 3 The value fluctuates between .
[0028] The oxides which may be used in the glass are the oxides of silicon, boron, aluminum, sodium, barium, vanadium, titanium, lanthanum, strontium, zirconium, potassium, magnesium, iron, calcium, zinc, lithium, barium and lead. The spherical glass beads may include, for example, various combinations of silica (SiO2), boron oxide (BO3), phosphorus pentoxide (PO5), vanadium pentoxide (VO5), arsenic trioxide (As2O3), germanium oxide (GeO2), calcium oxide (CaO), sodium oxide (Na2O), magnesium oxide (MgO), zinc oxide (ZnO), aluminum oxide (Al2O3), potassium oxide (KO), iron oxide (Fe2O3), lead oxide (PbO), barium oxide (BaO), barium titanate (BaTiO3), titanium oxide (TiO2), lithium oxide (Li2O), strontium oxide (SrO), lanthanum oxide (La2O3), and zirconium oxide (ZrO2). Silica and boron oxide are generally the least dense. Thus, glasses containing a high weight percentage of these oxides generally result in glass beads with a low refractive index. The refractive index can be increased by adding higher molecular weight oxides.
[0029] Preferably, the spherical glass beads are PbO-free.
[0030] Glass beads having a refractive index in the range of 1.5 to 2.51 and their composition in terms of oxides are disclosed in WO 2014 / 109564 A1, which is incorporated herein by reference in its entirety. PbO-free transparent glass beads having a refractive index greater than 2.15 are disclosed in U.S. Pat. No. 4,082,427, which is incorporated herein by reference in its entirety.
[0031] The spherical glass beads may be colored spherical glass beads as long as they maintain transparency. Both colored spherical glass beads made of colored transparent glass and spherical glass beads with a concentric transparent colored coating are included in the present invention. The color may be a natural color brought about by the composition of oxides, or may be intentionally selected by adding a component with a specific color. Colored glass beads with high refractive index and high transparency are disclosed in WO 2014 / 109564 A1.
[0032] Thus, in one embodiment, at least some of the spherical glass beads are made of a colored transparent glass and / or at least some of the spherical glass beads are coated with a concentric transparent colored coating.
[0033] The spherical glass beads have a median particle diameter D50 as measured by laser diffraction. The median particle diameter D50 is therefore the volume median based on the volume distribution. The median particle diameter D50 is the diameter below which half of the population of spherical glass beads falls. This volume median particle diameter is often referred to in the art as Dv50 or D v0.5 It is called.
[0034] In a preferred embodiment, the spherical glass beads have a median particle diameter D50 measured by laser diffraction of 25-100 μm, preferably 30-75 μm, more preferably 35-50 μm.
[0035] In another preferred embodiment, the spherical glass beads have a median particle diameter D50 measured by laser diffraction of 5 to 100 μm, for example 5 to 75 μm, 5 to 50 μm, 5 to 45 μm, 5 to 40 μm or 5 to 35 μm.
[0036] In another embodiment, the spherical glass beads have a median particle diameter D50 measured by laser diffraction of 5 to 1400 μm, for example 5 to 1200 μm, 5 to 1000 μm, 5 to 800 μm, 5 to 500 μm, or 5 to 300 μm.
[0037] In yet another preferred embodiment, the spherical glass beads have a median particle diameter D50 measured by laser diffraction of 25-150 μm, for example 50-150 μm, 75-150 μm, 100-150 μm, 110-150 μm or 115-150 μm.
[0038] The diameters D10 and D90 are often referred to in the art as Dv10 or D v0.1 and Dv90 or D v0.9 The D10 diameter is the diameter below which 10% of a population of spherical glass beads fall. Similarly, the D90 diameter is the diameter below which 90% of a population of spherical glass beads fall.
[0039] The span of the particle size distribution of spherical glass beads as measured by laser diffraction is defined as follows:
number
[0040] In a further preferred embodiment, the spherical glass beads have a median particle diameter D50 of 25-100 μm measured by laser diffraction and a span of 0-1, preferably 0-0.7, more preferably 0-0.5, even more preferably 0-0.2, even more preferably 0-0.1. In a more preferred embodiment, the spherical glass beads have a median particle diameter D50 of 30-75 μm measured by laser diffraction and a span of 0-1, preferably 0-0.7, more preferably 0-0.5, even more preferably 0-0.2, even more preferably 0-0.1. In an even more preferred embodiment, the spherical glass beads have a median particle diameter D50 of 35-50 μm measured by laser diffraction and a span of 0-1, preferably 0-0.7, more preferably 0-0.5, even more preferably 0-0.2, even more preferably 0-0.1.
[0041] In another more preferred embodiment, the spherical glass beads have a median particle diameter D50 of 5-35 μm as measured by laser diffraction and a span of 0-2, such as 0-1.8, 0-1.5, 0-1.25 and 0-1, or such as 0.5-2, 1-2 and 1.25-2.
[0042] In another even more preferred embodiment, the spherical glass beads have a median particle diameter D50 of 10-25 μm as measured by laser diffraction and a span of 0-2, such as 0-1.8, 0-1.5, 0-1.25 and 0-1, or such as 0.5-2, 1-2 and 1.25-2.
[0043] As will be appreciated by those skilled in the art, span=0 corresponds to monodisperse spherical glass beads.
[0044] In a preferred embodiment, at least a portion of the spherical glass beads are hemispherically coated with a light-reflecting coating. One example is a hemispherical aluminum coating. This is possible, but not necessary to provide the benefits described herein. Thus, in one embodiment, the spherical glass beads are not hemispherically coated with a light-reflecting coating. In another embodiment, at least a portion of the spherical glass beads are silane coated. In another embodiment, at least a portion of the spherical glass beads are silicone coated.
[0045] In a preferred embodiment, the amount of spherical glass beads is 60-78 wt. %, more preferably 61-76 wt. %, and even more preferably 62-74 wt. %, based on the total weight of the aqueous pseudoplastic gel composition provided in step (b).
[0046] In an embodiment, the amount of spherical glass beads is 60-78% by weight, 60-76% by weight, 60-74% by weight, 60-72% by weight, 60-70% by weight, 60-68% by weight, or 60-66% by weight, based on the total weight of the aqueous pseudoplastic gel composition.
[0047] In other embodiments, the amount of spherical glass beads is 62-80% by weight, 64-80% by weight, 66-80% by weight, 68-80% by weight, 70-80% by weight, 72-80% by weight, 74-80% by weight, or 76-80% by weight, based on the total weight of the aqueous pseudoplastic gel composition.
[0048] In a preferred embodiment, the aqueous pseudoplastic gel composition provided in step (b) comprises spherical glass beads having a refractive index measured at a wavelength λ of 589 nm of 1.9 to 2.6, more preferably 1.9 to 2.2.
[0049] In another embodiment, the aqueous pseudoplastic gel composition provided in step (b) comprises at least two types of spherical glass beads, at least one type of spherical glass beads having a refractive index measured at a wavelength λ of 589 nm between 1.8 and less than 2.0, and at least one further type of spherical glass beads having a refractive index measured at a wavelength λ of 589 nm between 2.0 and 2.8.
[0050] (Thickener) The aqueous pseudoplastic gel composition provided in step (b) includes a thickening agent, which may be the same thickening agent applied in step (d). In embodiments, the thickening agent applied in step (d) is the same thickening agent applied in the aqueous pseudoplastic gel composition provided in step (b). In other embodiments, the thickening agent applied in step (d) is different from the thickening agent applied in the aqueous pseudoplastic gel composition provided in step (b).
[0051] Without wishing to be bound by any theory, it is believed that the thickening agent limits or prevents settling and / or settling of the spherical glass beads, and optionally further particulate matter, in the aqueous pseudoplastic gel composition and in the final aqueous paste, ink, paint or coating formulation having retroreflective properties. Additionally, without wishing to be bound by any theory, it is believed that the thickening agent provides shear thinning behavior to the aqueous gel composition provided in step (b).
[0052] In an embodiment, the thickening agent in the aqueous pseudoplastic gel composition provided in step (b) and / or the thickening agent applied in step (d) comprises a mixture of different thickening agents. In a preferred embodiment, the thickening agent in the aqueous pseudoplastic gel composition provided in step (b) consists of a single thickening agent. In a preferred embodiment, the thickening agent applied in step (d) consists of a single thickening agent.
[0053] One preferred group of thickeners are ASE polymers (alkali swellable emulsions; these polymers are produced using emulsion polymerization). ASE polymers are based on a balance of hydrophilic (meth)acrylic acid monomers and hydrophobic (meth)acrylate ester monomers and can be supplied at high volumetric solids in liquid form. ASE polymers rely on a change from low to high pH (neutralization) to induce thickening. The "inducer" is incorporated into the polymer by forming an approximately 50:50 ratio of water-soluble (meth)acrylic acid and water-insoluble (meth)acrylate esters. If the acid is not neutralized (low pH), the polymer is water insoluble and will not thicken. If the acid is fully neutralized (high pH), the polymer becomes soluble and thickens. ASE polymers are supplied at low pH (<5) and maintain low as-supplied viscosity (<100 cP) at up to 35% solids. When subjected to a pH of about 7 or higher, ASE polymers solubilize, swell and thicken compositions by volume exclusion. The degree of thickening can be related to the molecular weight of the polymer. ASE polymers, whose performance depends on water absorption and swelling, tend to be of very high molecular weight, which allows them to thicken efficiently. The rheological profile that ASE polymers form typically exhibits rapid shear thinning (pseudoplasticity), making them well suited to impart high viscosity at very low shear rates.
[0054] In one embodiment, the hydrophilic monomer of the ASE polymer is selected from the group consisting of (meth)acrylic acid, maleic acid, and combinations thereof.
[0055] In another embodiment, the hydrophobic monomers of the ASE polymer are selected from the group consisting of esters of (meth)acrylic acid with C1-C4-alcohols, in particular ethyl acrylate, butyl acrylate and methyl methacrylate.
[0056] In yet another preferred embodiment, the hydrophilic monomer of the ASE polymer is selected from the group consisting of (meth)acrylic acid, maleic acid and combinations thereof, and the hydrophobic monomer of the ASE polymer is selected from the group consisting of esters of (meth)acrylic acid with C1-C4-alcohols, in particular ethyl acrylate, butyl acrylate and methyl methacrylate.
[0057] In one embodiment, the ASE polymer is a copolymer consisting of 10-90% by weight, based on the weight of the ASE polymer, of repeat units based on one or more hydrophilic monomers A and 10-90% by weight of repeat units based on one or more hydrophobic monomers B, the amounts of monomers A and B adding up to 100% by weight: [ka] [wherein R1 and R2 are independently hydrogen or methyl, and R3 is C1-C4-alkyl].
[0058] Another preferred group of thickeners are HASE polymers (hydrophobically modified alkali swellable emulsions, these polymers are produced using emulsion polymerization). HASE polymers are copolymers based on ASE polymer chemistry by adding one or more hydrophobic associative monomers, such as acrylic esters and / or vinyl ester monomers, to the ASE polymer composition. HASE polymers retain the pH-dependent behavior of their ASE counterparts, but they also thicken by hydrophobic association in addition to water absorption. This mechanism is known as associative thickening (i.e., they associate with any hydrophobic moieties in the composition).
[0059] The hydrophilic and hydrophobic monomers of the HASE polymers may be the same as those described for the ASE polymers. Preferred hydrophobic associative monomers are (meth)acrylic acid and C8-C 22 - (meth)acrylic acid ester monomers of alcohols and / or (substituted) vinyl alcohols and C8-C 22In another preferred embodiment, the one or more hydrophobic associative monomers are selected from the group consisting of steareth-20 methacrylate, beheneth-25 methacrylate, vinyl neodecanoate, and combinations thereof.
[0060] In one embodiment, the HASE polymer is a copolymer consisting of 10-90% by weight, based on the weight of the HASE polymer, of repeat units based on one or more hydrophilic monomers A as defined hereinbefore, 10-90% by weight of repeat units based on one or more hydrophobic monomers B as defined hereinbefore, and 0.01-2% by weight of repeat units based on one or more hydrophobic associative monomers C and / or D, the amounts of monomers A, B, C and D adding up to 100% by weight: [ka] [In the formula, R4 is hydrogen or methyl, and R5 is a C8-C 22 -alkyl, n is an integer from 0 to 50, R6 is hydrogen or methyl, and R7 is C8 to C 22 -alkyl].
[0061] Yet another preferred group of thickeners are hydrophobically modified ethoxylated urethane (HEUR) polymers. Unlike ASE or HASE type thickeners, HEUR polymers are non-ionic and soluble at any pH. This solubility is due to the ethylene oxide backbone of the polymer, which is water-soluble and constitutes the majority of the polymer structure. Therefore, HEUR polymers require hydrophobic moieties in the composition to interact with the ethylene oxide backbone to provide structure.
[0062] Examples of ASE polymers include Rheovis® 1125 (available from BASF Corporation), ACULYN™ 33; ACULYN™ 38, ACUSOL™ 810A, ACULYN™ 830, ACULYN™ 835, ACULYN™ 842 (all available from DOW Chemical), and Carbopol® Aqua 30 polymer (manufactured by Lubrizol Corporation).
[0063] Examples of HASE polymers include ACRYSOL™ Excel, ACRYSOL™ TT615, ACRYSOL™ 22; ACRYSOL™ 88, ACUSOL™ 801S, ACUSOL™ 805S, ACUSOL™ 820 and ACUSOL™ 823 (all available from DOW Chemical).
[0064] Examples of HEUR polymers include Accusol™ 880, Accusol™ 882, Accuryn™ 44, and Accuryn™ 46N (all available from DOW Chemical).
[0065] In yet another embodiment, the thickening agent is selected from the group consisting of acrylate crosspolymers, crosslinked polyacrylic acid polymers and crosslinked polyacrylic acid copolymers, in particular from the Carbopol® polymer products manufactured by Lubrizol Corporation, such as Carbopol® Aqua SF-1 Polymer, Carbopol® Aqua SF-1 OS Polymer and Carbopol® Aqua SF-3 Polymer.
[0066] In yet another embodiment, the thickening agent is selected from the group consisting of liquid acrylic crosslinked or copolymer dispersions.
[0067] In yet another embodiment, the thickening agent is selected from non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, such as Aquatix 8421 available from BYK.
[0068] In yet another embodiment, the thickener is selected from modified urea or urea modified polyamide, such as Rheobyk-420 available from BYK.
[0069] In one embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, acrylate crosspolymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, modified ureas or urea modified polyamides, and combinations thereof.
[0070] In another embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, acrylate crosspolymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, and combinations thereof.
[0071] In another embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, and combinations thereof.
[0072] In yet another embodiment, the thickening agent is selected from the group consisting of ASE polymers, HASE polymers, and combinations thereof. In one embodiment, the thickening agent is selected from the group consisting of ASE polymers and combinations thereof. In another embodiment, the thickening agent is selected from the group consisting of HASE polymers and combinations thereof.
[0073] In a preferred embodiment, the amount of thickener in the aqueous pseudoplastic gel composition provided in step (b) is 0.20 to 2.45 wt %, more preferably 0.40 to 2.25 wt %, and even more preferably 0.75 to 2.10 wt %, based on the total weight of the aqueous pseudoplastic gel composition.
[0074] In embodiments, the amount of thickener is 0.15 to 2.45 wt %, 0.15 to 2.25 wt %, 0.15 to 2.1 wt %, 0.15 to 1.9 wt %, 0.15 to 1.7 wt %, 0.15 to 1.5 wt %, 0.15 to 1.4 wt %, or 0.15 to 1.3 wt %, based on the total weight of the aqueous pseudoplastic gel composition.
[0075] In other embodiments, the amount of thickener is 0.20-2.5 wt%, 0.25-2.5 wt%, 0.30-2.5 wt%, 0.35-2.5 wt%, 0.40-2.5 wt%, 0.45-2.5 wt%, 0.50-2.5 wt%, 0.55-2.5 wt%, 0.60-2.5 wt%, 0.65-2.5 wt%, 0.70-2.5 wt%, 0.75-2.5 wt%, or 0.80-2.5 wt%, based on the total weight of the aqueous pseudoplastic gel composition.
[0076] The amount of water in the aqueous pseudoplastic gel composition provided in step (b) is specified independently. When the thickener is applied, for example, in the form of a dispersion in water, the amount of thickener defined hereinbefore relates to the dry weight of the thickener.
[0077] In a preferred embodiment, the mixture obtained in step (c) is mixed in step (d) with 0-1.9 wt%, 0-1.8 wt%, 0-1.7 wt%, 0-1.6 wt%, 0-1.5 wt%, 0-1.4 wt%, or 0-1.3 wt% of a thickener, based on the total weight of the aqueous paste, ink, paint or coating formulation having retroreflective properties.
[0078] In another preferred embodiment, the mixture obtained in step (c) is mixed in step (d) with 0.1-2.0 wt.%, 0.2-2.0 wt.%, 0.3-2.0 wt.%, 0.4-2.0 wt.%, or 0.5-2.0 wt.% of a thickener, based on the total weight of the aqueous paste, ink, paint or coating formulation having retroreflective properties.
[0079] In a preferred embodiment, the thickener applied in step (d) is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, acrylate crosspolymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, modified ureas or urea modified polyamides, and combinations thereof, as previously defined herein.
[0080] (Additional Ingredients) In a preferred embodiment, the one or more additional ingredients in the aqueous pseudoplastic gel composition provided in step (b) are selected from the group consisting of foam control agents, humectants, preservatives, dyes, luminescent agents, such as phosphorescent and fluorescent agents, pigments, UV absorbers, neutralizing agents, binders and resins, mica flake pigments, and metal flakes or powders. Preferably, the one or more additional ingredients in the aqueous pseudoplastic gel composition provided in step (b) are selected from the group consisting of foam control agents, preservatives, and neutralizing agents.
[0081] Non-limiting examples of humectants that can be used are 2,3-propanediol, ethylene glycol, and butylene glycol.
[0082] Examples of binders and resins that may be used are aqueous binders and resins, such as aqueous dispersions of binders and resins. In a preferred embodiment, the aqueous pseudoplastic gel composition provided in step (b) does not contain any binders or resins.
[0083] Metal flakes or powders can be used as reflective pigments, examples being aluminum, bronze, copper, gold, silver, tin and nickel flakes, preferably aluminum flakes.
[0084] Mica flake pigments, for example pearlescent pigments based on mica flakes, can also be used as reflective pigments.
[0085] In embodiments, the amount of one or more further components is 0-4.5 wt.%, 0-4.0 wt.%, 0-3.5 wt.%, 0-3.0 wt.%, 0-2.5 wt.%, 0-2.0 wt.%, 0-1.5 wt.%, 0-1.0 wt.%, or 0-0.5 wt.%, based on the total weight of the aqueous pseudoplastic gel composition provided in step (b).
[0086] In other embodiments, the amount of one or more additional components is 0.01-5 wt.%, 0.02-5 wt.%, 0.04-5 wt.%, 0.08-5 wt.%, 0.15-5 wt.%, 0.25-5 wt.%, 0.35-5 wt.%, 0.45-5 wt.%, or 0.55-5 wt.%, based on the total weight of the aqueous pseudoplastic gel composition.
[0087] The amount of water in the aqueous pseudoplastic gel composition provided in step (b) is specified independently. If the one or more further components are applied, for example, in the form of a dispersion in water, the amount of the one or more further components defined herein above relates to the dry weight, i.e. water-free weight, of the one or more further components.
[0088] (Rheological behavior) The aqueous gel composition prepared in step (b) has pseudoplastic behavior, i.e., shear-thinning behavior without exhibiting a yield point. This means that the composition is gel-like but still capable of flowing in static / stable conditions (no shear) and is also gel-like (and capable of flowing) at increased shear rates. In other words, the aqueous gel composition is gel-like but is nevertheless pourable. Furthermore, when the static / stable conditions are disturbed by subjecting the gel to a certain increased shear rate, the viscosity decreases (shear-thinning behavior).
[0089] The aqueous pseudoplastic gel composition provided in step (b) is preferably characterized by a tan(δ) value of less than 1 at an oscillation frequency of 10-0.1 Hz, measured in a rheometer with plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C. In a preferred embodiment, the tan(δ) value is between 0.05 and 0.9, more preferably between 0.1 and 0.8, measured in a rheometer with plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C. at an oscillation frequency of 10-0.1 Hz.
[0090] As will be appreciated by those skilled in the art, the tan(δ) value is measured at a suitable shear strain within the linear viscoelastic range.
[0091] As previously defined herein, the aqueous pseudoplastic gel composition provided in step (b) may have a viscosity of 0.01 s -1 The first viscosity η2 of 5 to 250 Pa·s at a shear rate of 100 s -1The composition has a second viscosity η3 that is 10 to 1000 times lower than the first viscosity at a shear rate of 100 / s. In a preferred embodiment, the first viscosity is 10 to 230 Pa·s, more preferably 14 to 220 Pa·s, even more preferably 16 to 210 Pa·s, even more preferably 18 to 200 Pa·s, and even more preferably 20 to 190 Pa·s. In another preferred embodiment, the second viscosity is 0.05 to 3 Pa·s, more preferably 0.08 to 2 Pa·s, even more preferably 0.1 to 1.5 Pa·s, even more preferably 0.12 to 1.2 Pa·s, even more preferably 0.15 to 1.0 Pa·s, and most preferably 0.2 to 0.8 Pa·s.
[0092] In another embodiment, the aqueous pseudoplastic gel composition provided in step (b) has a pH of 0.01 to 1. -1 The first viscosity η2 of 100 to 250 Pa s at a shear rate of 100 s -1 has a second viscosity η3 that is 200 to 600 times lower than the first viscosity at a shear rate of
[0093] In another embodiment, the aqueous pseudoplastic gel composition provided in step (b) has a pH of 0.01 to 1. -1 The first viscosity η2 of 100 to 250 Pa s at a shear rate of 100 s -1 The viscosity of the polymer solution is 0.15 to 1.0 Pa·s, and preferably 0.2 to 0.8 Pa·s, at a shear rate of 0.5 to 1.0 Pa·s.
[0094] The gel structure of the aqueous pseudoplastic gel composition prepared in step (b) and the 0.01s -1 The first viscosity η2, determined at a shear rate of 1000 rpm, is sufficient to maintain the spherical glass beads and optional additional particulate material in suspension for an extended period of time.
[0095] The present inventors have found that the aqueous pseudoplastic gel composition prepared in step (b) is stable for 100 s -1 It was confirmed that the first viscosity was regained in a relatively short time after the application of a shear rate of 100 MPa (thixotropy test).
[0096] Thus, in a preferred embodiment, the aqueous pseudoplastic gel composition provided in step (b) has a pH of 0.1 s -1 and the aqueous pseudoplastic gel composition has a third viscosity η4 at a shear rate of (i) The aqueous pseudoplastic gel composition is dissolved in water for 0.1 s. -1 for at least 30 seconds and measuring a third viscosity η4; (ii) The aqueous pseudoplastic gel composition is -1 for 30 seconds; (iii) Shear rate is reduced to 0.1 s -1 to (iv) measuring the viscosity of the aqueous pseudoplastic gel composition as a function of time and comparing it to the value of the third viscosity, η4. regains at least 20%, preferably at least 30%, more preferably at least 50%, even more preferably at least 70% of the value of the third viscosity η4 within 10 s, preferably within 5 s, more preferably within 2 s of the reduction in shear rate in step (iii) of the process comprising the successive steps of: The viscosity is measured at a temperature of 25° C. in a rheometer with plate-plate geometry and a gap distance of 0.5 mm.
[0097] The phrase "regain at least x% of the value of the third viscosity η4 within a certain time" when used in the context of the present invention means that the viscosity actually reaches a value of x×η4 / 100 within that time.
[0098] This embodiment can also be stated as follows: In a preferred embodiment, the aqueous pseudoplastic gel composition provided in step (b) is 0.1 s -1 and the aqueous pseudoplastic gel composition has a third viscosity η4 at a shear rate of (i) The aqueous pseudoplastic gel composition is dissolved in water for 0.1 s. -1 for at least 30 seconds and measuring a third viscosity η4; (ii) The aqueous pseudoplastic gel composition is -1 for 30 seconds; (iii) Shear rate is reduced to 0.1 s -1 to (iv) measuring a fourth viscosity η5 of the aqueous pseudoplastic gel composition as a function of time. reaches, exhibits or has a fourth viscosity η5 of at least 20%, preferably at least 30%, more preferably at least 50%, even more preferably at least 70% of the value of the third viscosity η4 within 10 s, preferably within 5 s, more preferably within 2 s of reducing the shear rate in step (iii) of the process comprising the successive steps of: The viscosity is measured at a temperature of 25° C. in a rheometer with plate-plate geometry and a gap distance of 0.5 mm.
[0099] In an embodiment, the aqueous pseudoplastic gel composition provided in step (b) regains at least 20%, preferably at least 30%, more preferably at least 50%, even more preferably at least 70%, and even more preferably at least 90% by weight of the value of the third viscosity η4 within 10 s of reducing the shear rate in step (iii).
[0100] In an embodiment, the aqueous pseudoplastic gel composition provided in step (b) regains at least 20%, preferably at least 30%, more preferably at least 50% of the value of the third viscosity η4 within 5 s of reducing the shear rate in step (iii).
[0101] In an embodiment, the aqueous pseudoplastic gel composition provided in step (b) regains at least 20%, preferably at least 30%, of the value of the third viscosity η4 within 2 s of reducing the shear rate in step (iii).
[0102] As will become apparent from the accompanying examples, the aqueous pseudoplastic gel composition provided in step (b) can regain about 100% of the value of the third viscosity η4 after a period of time following the reduction in shear rate in step (iii).
[0103] Process for the preparation of aqueous pseudoplastic gel compositions The aqueous pseudoplastic gel composition provided in step (b) may be prepared as follows. Generally speaking, the components of the aqueous pseudoplastic gel composition may be added in any order. After mixing all the components, the composition is preferably stirred or homogenized at a temperature of 15-30° C. for a period of preferably 5-15 minutes. In a preferred embodiment, the thickener is added after mixing the water, spherical glass beads and any further components. The stirring or homogenization is preferably performed at a low shear rate to avoid the incorporation of air bubbles into the aqueous pseudoplastic gel composition.
[0104] As previously explained herein, the thickening effect of the thickening agent may depend on the pH value. Thus, the process for the preparation of an aqueous pseudoplastic gel composition may include a step of adjusting the pH, for example adjusting the pH to a value between 6.0 and 11, for example between 6.5 and 11, 7.0 and 11, 6.5 and 9.5, 7.5 and 10.5, or 7.4 and 7.9. The pH may be suitably adjusted using dilute NaOH or an aminomethylpropanol neutralizing agent, for example AMP Ultra® PC2000.
[0105] In one embodiment, the aqueous pseudoplastic gel composition provided in step (b) comprises (i) adding water, spherical glass beads as defined hereinbefore, a thickening agent as defined hereinbefore, and optionally one or more further ingredients as defined hereinbefore to a vessel; (ii) stirring or homogenizing the mixture obtained in step (i) at a temperature preferably between 15 and 30° C. for a period preferably between 5 and 15 minutes; and (iii) optionally, before or after step (ii), adjusting the pH, preferably to a value between 6.0 and 11, more preferably between 6.5 and 11, even more preferably to a value between 7.0 and 11. The composition is prepared using a process comprising:
[0106] In an embodiment, the pH in step (iii) is adjusted to a value between 6.5 and 9.5, in another embodiment, the pH in step (iii) is adjusted to a value between 7.5 and 10.5.
[0107] Thus, the present invention has been described with reference to certain specific embodiments discussed above, it being recognized that these embodiments are susceptible to various modifications and alternatives known to those skilled in the art.
[0108] Moreover, for the proper understanding of this specification and its claims, it should be understood that the verb "comprise" and its conjugations are used in an open-ended sense to mean that the items following the word are included, but items not specifically mentioned are not excluded. Furthermore, the reference of an element with the indefinite article "a" or "an" does not exclude the possibility that there are more than one of that element, unless the context clearly dictates that there is only one of that element. Thus, the indefinite article "a" or "an" generally means "at least one." EXAMPLES
[0109] [Example 1] Three aqueous pseudoplastic gel compositions were prepared by adding the ingredients to a container at ambient temperature (approximately 20° C.) in the following order: (1) demineralized water, (2) preservative (additional ingredient), (3) spherical glass beads, (4) AMP Ultra PC 2000 to adjust pH (additional ingredient), and (5) thickener. The resulting mixture was stirred for approximately 10 minutes, also at ambient temperature. The amounts of the various ingredients are listed in Table 1. The following ingredients were used:
[0110] (spherical glass beads) It has a refractive index of about 2.2 measured at a wavelength λ of 589 nm, a median particle diameter D50 of 40.37 μm, a D10 diameter of 37.32 μm and a D90 diameter of 44.11 μm measured by laser diffraction, and a molecular weight of about 4.5 g / cm 3SFX2.2 obtained from Jianxi Sunflex Light Retroreflective Material Co, Ltd. These spherical glass beads contain TiO2, BaO, ZnO and CaO.
[0111] (Additional Ingredients) AMP Ultra PC 2000 obtained from Angus Chemical Company; neutralizer Acticide MBL obtained from Thor; a preservative
[0112] (Thickener) Carbopol® Aqua SF-1, a crosslinked acrylate copolymer thickener, obtained from Lubrizol Rheovis® AS1152, an ASE thickener, obtained from BASF Accurin™ Excel, a HASE thickener, obtained from DOW Chemical
[0113] [Table 1]
[0114] [Example 2] The stability of the three aqueous pseudoplastic gel compositions shown in Table 1 was determined by visual and tactile inspection to see if the samples exhibited settling, syneresis, or separation (phase or otherwise). A sample was considered stable if no settling, syneresis, or separation was observed upon visual and tactile inspection. The pH of the three aqueous pseudoplastic gel compositions immediately after synthesis, and their subsequent stability, are listed in Table 2.
[0115] [Table 2]
[0116] [Example 3] The rheological behavior of the three aqueous pseudoplastic gel compositions of Example 1 was measured at a temperature of 25.0° C. using a Malvern Kinexus rheometer with plate-plate geometry (PL40 plates) and a gap distance of 0.5 mm.
[0117] The viscosity versus shear rate profiles of three aqueous pseudoplastic gel compositions according to the present invention were measured using 10 samples per 100 samples at about 0.001 s -1 ~100s -1 The viscosity versus shear rate profiles are shown in Figure 1. As can be inferred from Figure 1, all of the aqueous pseudoplastic gel compositions exhibit shear-shear behavior. The shape of the viscosity versus shear rate profiles in the zero shear rate limit suggests that the compositions do not have a yield point. All three aqueous pseudoplastic gel compositions were pourable.
[0118] The thixotropy test was then carried out by applying three shear rate regimes and measuring the viscosity as a function of time. In the first regime, the viscosity was measured at 0.1 s for a period of about 50 to 60 s. -1 In the second mode, a shear rate of 100 s was applied and the viscosity was measured with a sampling interval of 2 s. -1 In the third mode, the shear rate was increased to 0.1 s and the viscosity was measured for 30 s with a sampling interval of 2 s. -1 The viscosity was measured for at least 40 seconds with a sampling interval of 1 second. Figure 2 shows the thixotropic behavior of the three aqueous pseudoplastic gel compositions of Example 1. As can be inferred from Figure 2, the aqueous pseudoplastic gel compositions all recover at least 50% of the viscosity measured in the first mode within a few seconds of the onset of the third mode. Furthermore, the aqueous pseudoplastic gel compositions can recover about 100% of the viscosity value in the first mode.
[0119] Additionally, frequency sweep studies were performed to evaluate the four viscoelastic behaviors of the aqueous pseudoplastic gel compositions. The loss modulus G”, storage modulus G’ and tan(δ) were measured on 10 samples per 10 at preferred shear strains within the linear viscoelastic range and oscillation frequencies varying between 10 Hz and 0.1 Hz. The results are shown in Figure 3. The tan(δ) values are all less than 1 over the oscillation frequency range, indicating gel-like behavior in that the elastic behavior dominates over the viscous behavior.
[0120] [Example 4] The three aqueous pseudoplastic gel compositions of Example 1 were used to prepare six different compositions selected from the group consisting of water-based paste, ink, paint or coating formulations having retroreflective properties.
[0121] The three aqueous pseudoplastic gel compositions of Example 1 were mixed with several commercial products listed in Table 3. The gels were mixed at 0.01 s at a temperature of 25° C. in a rheometer with plate-plate geometry and a gap distance of 0.5 mm. -1 The viscosities η1 of the commercial products measured at a shear rate of 100 rpm are also shown in Table 3.
[0122] [Table 3]
[0123] If necessary, additional thickening agent (selected from those listed in Example 1) was added.
[0124] Mixing was performed as follows: A commercially available water-based paste, ink, paint or coating formulation was placed in a beaker. The water-based pseudoplastic gel composition was then added, followed by thorough mixing with a Dispermill Orange-line 18 / 186 at 2000 rpm for 10 minutes. In the next step, additional thickener was added, followed by thorough mixing again with a Dispermill Orange-line 18 / 186 at 3400 rpm for 10 minutes. The entire process was carried out at ambient temperature (approximately 20° C.).
[0125] The amounts of the various components in the resulting compositions are listed in Table 4.
[0126] [Table 4]
[0127] The stability of six different compositions selected from the group consisting of water-based paste, ink, paint or coating formulations with retroreflective properties was determined by visual and tactile inspection to see if the samples showed settling, syneresis or separation (phase or otherwise). A composition is considered stable if no settling, syneresis or separation is observed by visual and tactile inspection. The amount of spherical glass beads in the various compositions, their pH immediately after synthesis, and their subsequent stability are listed in Table 5.
[0128] [Table 5]
[0129] [Example 6] Composition T00469B was applied to wallpaper using spray coating. A retroreflective wallpaper with visually appealing properties was obtained.
[0130] Composition T00475 was applied to fabric using screen printing, resulting in a visually appealing printed textile product with retroreflective properties.
[0131] Composition T00466B was applied to wallpaper using screen printing. A visually appealing printed wallpaper with retroreflective properties was obtained.
[0132] [Comparative Example] Five comparative retroreflective compositions were prepared by directly mixing a composition selected from the group consisting of water-based paste, ink, paint or coating formulations (as defined in Example 4) with spherical glass beads (SFX2.2). The comparative retroreflective compositions were prepared as follows: A commercially available water-based paste, ink, paint or coating formulation was placed in a beaker. The spherical glass beads were then added, followed by thorough mixing with a Dispermill Orange Line 18 / 186 at 2000 rpm for 10 minutes. The process was carried out at ambient temperature (approximately 20° C.). The amounts of the various components in the resulting comparative compositions are listed in Table 6.
[0133] [Table 6]
[0134] The stability of the five comparative compositions was determined by visual and tactile inspection to determine whether the samples exhibited settling, syneresis, or separation (phase or otherwise). In addition, it was determined whether the samples maintained homogeneity. The pH immediately after synthesis, as well as the subsequent stability and homogeneity, are listed in Table 7.
[0135] [Table 7]
Claims
1. 1. A method for providing a composition selected from the group consisting of water-based pastes, inks, paints and coating formulations having retroreflective properties, said method comprising: a) providing a water-based paste, ink, paint or coating formulation having no retroreflective properties, said water-based paste, ink, paint or coating formulation having a reflectance of less than 0.01 s -1 Viscosity η of 0.25 to 1000 Pa·s at a shear rate of 1 and b) 0.01 s -1 A first viscosity η of 5 to 250 Pa s at a shear rate of 2 and 100s -1 The first viscosity η 2 A second viscosity η that is 10 to 1000 times lower than 3 providing an aqueous pseudoplastic gel composition having, based on the total weight of the aqueous pseudoplastic gel composition: 15 to 39.85% by weight of water, 60-80% by weight of spherical glass beads having a median particle diameter D50 of 5-1500 μm as measured by laser diffraction and a refractive index of 1.8-2.8 as measured at a wavelength λ of 589 nm, optionally at least a portion of said spherical glass beads being hemispherically coated with a light reflective coating; 0.15 to 2.5% by weight of a thickening agent, and 0-5% by weight of one or more further ingredients and c) mixing the aqueous paste, ink, paint or coating formulation provided in step (a) with the aqueous pseudoplastic gel composition provided in step (b) in a weight ratio of 30:70 to 70:30; d) mixing the mixture obtained in step (c) with 0-2 wt. % of a thickener, based on the total weight of said aqueous paste, ink, paint or coating formulation having retroreflective properties, to provide an aqueous paste, ink, paint or coating formulation having retroreflective properties; The viscosity η 1 , η 2 and η 3 is measured at a temperature of 25° C. in a rheometer with plate-plate geometry and a gap distance of 0.5 mm.
2. The aqueous pseudoplastic gel composition prepared in step (b) is -1 The third viscosity η 4 The aqueous pseudoplastic gel composition comprises: (i) The aqueous pseudoplastic gel composition is mixed with water for 0.1 s. -1 for at least 30 seconds, and a third viscosity η 4 measuring the (ii) The aqueous pseudoplastic gel composition is mixed with water for 100 s. -1 for 30 seconds; (iii) Shear rate is 0.1 s -1 to (iv) measuring the viscosity of the aqueous pseudoplastic gel composition as a function of time. A third viscosity η is obtained within 10 s of reducing the shear rate in step (iii) of the process comprising the successive steps of 4 2. The method of claim 1, wherein the at least one of the first and second values of
3. 3. The method of claim 1 or 2, wherein the aqueous pseudoplastic gel composition provided in step (b) has a tan(δ) value of less than 1 measured in a rheometer having a plate-plate geometry and a gap distance of 0.5 mm at a temperature of 25° C. and an oscillation frequency of 10 to 0.1 Hz.
4. 4. The method according to claim 1, wherein the spherical glass beads in the aqueous pseudoplastic gel composition provided in step (b) have a refractive index measured at a wavelength λ of 589 nm of 1.9 to 2.
6.
5. 5. The method of claim 1, wherein the aqueous pseudoplastic gel composition provided in step (b) comprises 0.20 to 2.45 wt. % of a thickening agent, based on the total weight of the aqueous pseudoplastic gel composition.
6. 6. The method of any one of claims 1 to 5, wherein the thickening agent in the aqueous pseudoplastic gel composition provided in step (b) is selected from the group consisting of ASE polymers, HASE polymers, HEUR polymers, liquid acrylic crosslinked or copolymer dispersions, acrylate crosspolymers, crosslinked polyacrylic acid polymers, crosslinked polyacrylic acid copolymers, non-ionic aqueous emulsions of modified ethylene vinyl acetate copolymer waxes, modified ureas or urea modified polyamides, and combinations thereof.
7. 7. The method according to any one of claims 1 to 6, wherein the aqueous paste, ink, paint or coating formulation with retroreflective properties obtained in step (d) is stable and homogeneous for at least one day, and the composition is considered stable and homogeneous if no settling, syneresis and separation can be observed upon visual and tactile inspection, and no air inclusions can be visually observed upon inspection with a microscope camera.
8. The process according to any one of claims 1 to 7, wherein steps (c) and (d) are carried out at a temperature of from 15 to 30°C.
9. 9. The method according to any one of claims 1 to 8, wherein in step (c) the aqueous paste, ink, paint or coating formulation provided in step (a) is mixed with the aqueous pseudoplastic gel composition provided in step (b) in a weight ratio of 40:60 to 60:
40.
10. 10. The method according to any one of claims 1 to 9, wherein in step (d), the mixture obtained in step (c) is mixed with 0 to 1.7 wt. % of the thickener, based on the total weight of the water-based paste, ink, paint or coating formulation having retroreflective properties.
11. 10. The method according to any one of claims 1 to 9, wherein in step (d), the mixture obtained in step (c) is mixed with 0.4 to 2.0 wt. % of said thickener, based on the total weight of the aqueous paste, ink, paint or coating formulation having retroreflective properties.
12. The method according to any one of claims 1 to 11, further comprising applying the water-based paste, ink, paint or coating formulation having retroreflective properties obtained in step (d) to a substrate using screen printing, spray coating or spray painting.
13. The aqueous pseudoplastic gel composition provided in step (b) comprises: (A) adding water, said spherical glass beads, said thickening agent and optionally said one or more additional ingredients to a container; (B) stirring or homogenizing the mixture obtained in step (A); and (C) optionally adjusting the pH before or after step (B). The method of any one of claims 1 to 12, wherein the composition is prepared using a process comprising:
Citation Information
Patent Citations
JP1971003488Y1
Coating composition for road surface sign and construction method
JP2016089036A
Retroreflective coating, coated film and substrate
JP2017101194A
Reflective decorative surface coating and a decorative water-borne surface coating system having at least one basecoat
US20080044627A1
Retroreflective inks
WO2000042113A1